High-risk & critical care obstetrics - Troiano, Nan H.; Harvey, Carol J.; Chez, Bonnie Flood (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
"The edition includes extensive revisions that reflect evidence-based changes in clinical practice for specific complications, and new chapters have been added that address foundations for practice, adjuncts for clinical practice, and selected clinical guidelines"--Provided by publisher.
Sepsis in pregnancy / Julie M.R. Arafeh and Bonnie K. Dwyer -- Amniotic fluid embolus (anaphylactoid syndrome of pregnancy) / Renee' Jones and Steven L. Clark -- Perinatal infection / Patrick Duff -- Trauma in pregnancy / Donna Ruth and Richard S. Miller -- Maternal obesity : effects on pregnancy / Amy H. Picklesimer and Karen Dorman -- Appendix A: Guidelines for the initial assessment and triage of obstetric patients -- Appendix B: Guidelines for fetal heart rate monitoring -- Appendix C: Guidelines for use of fetal acoustic stimulation -- Appendix D: Guidelines for the care of patients in labor -- Appendix E: Guidelines for the care of patients with preterm labor -- Appendix F: Guidelines for the care of patients with diagnosed or suspected placenta previa during the peripartum period -- Appendix G: Guidelines for the care of obstetric patients with diabetic ketoacidosis (DKA) -- Appendix H: Guidelines for the care of patients with preeclampsia/eclampsia -- Appendix I: Guidelines for the care of patients requiring induction of labor with oxytocin -- Appendix J: Guidelines for the care of patients requiring induction of labor due to intrauterine fetal demise (IUFD) -- Appendix K: Guidelines for the care of the obstetric trauma patient -- Appendix L: Guidelines for the care of the obstetric patient requiring transport -- Appendix M: Guidelines for the care of the critically ill pregnant patient.
At head of title: AWHONN.
At head of title: AWHONN.
Rev. ed. of: High risk and critical care intrapartum nursing / [edited by] Lisa K. Mandeville, Nan H. Troiano. 2nd ed. c1999.
Rev. ed. of: High risk and critical care intrapartum nursing / [edited by] Lisa K. Mandeville, Nan H. Troiano. 2nd ed. c1999.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Keywords: Maternity nursing; Pregnancy -- Complications -- Nursing; Labor (Obstetrics) -- Complications -- Nursing; Obstetrical Nursing -- methods; Critical Care; Delivery, Obstetric -- nursing; Obstetric Labor Complications -- nursing; Pregnancy Complications -- nursing; Pregnancy, High-Risk.; Pregnancy; Electronic books